Adipose tissue-related proteins locally associated with resolution of inflammation in obese mice - Jilkova, Z M; Hensler, M; Medrikova, D; Janovska, P; Horakova, O; Rossmeisl, M; Flachs, P; Sell, H; Eckel, J; Kopecky, J (International journal of obesity (2005), 2014)
OBJECTIVE: Resolution of low-grade inflammation of white adipose tissue (WAT) is one of the keys for amelioration of obesity-associated metabolic dysfunctions. We focused on the identification of adipokines, which could be involved at the early stages of resolution of WAT inflammation. METHODS AND PROCEDURE: Male C57BL/6J mice with obesity induced in response to a 22-week feeding corn oil-based high-fat (cHF) diet were divided into four groups and were fed with, for 2 weeks, control cHF diet or cHF-based diets supplemented with: (i) concentrate of n-3 long-chain polyunsaturated fatty acids, mainly eicosapentaenoic and docosahexaenoic acids (cHF+F); (ii) thiazolidinedione drug rosiglitazone (cHF+TZD); and (iii) both compounds (cHF+F+TZD). RESULTS: The short-term combined intervention exerted additive effect in the amelioration of WAT inflammation in obese mice, namely in the epididymal fat, even in the absence of any changes in either adipocyte volume or fat mass. The combined intervention elicited hypolipidaemic effect and induced adiponectin, whereas the responses to single interventions (cHF+F, cHF+TZD) were less pronounced. In addition, analysis in WAT lysates using protein arrays revealed that the levels of a small set of adipose tissue-related proteins, namely macrophage inflammatory protein 1γ, endoglin, vascular cell adhesion molecule 1 and interleukin 1 receptor antagonist, changed in response to the anti-inflammatory interventions and were strongly reduced in the cHF+F+TZD mice. These results were verified using both the analysis of gene expression and enzyme-linked immunosorbent analysis in WAT lysates. In contrast with adiponectin, which showed changing plasma levels in response to dietary interventions, the levels of the above proteins were affected only in WAT. CONCLUSIONS: We identified several adipose tissue-related proteins, which are locally involved in resolution of low-grade inflammation and remodelling of WAT.
Keywords: energetický metabolismus; myši obézní; Male; Inflammation; kvantitativní polymerázová řetězová reakce; Obesity; kyseliny dokosahexaenové; Fatty Acids, Omega-3; Mice, Obese; obezita; thiazolidindiony; omega-3 mastné kyseliny; Adipocytes; Diet, High-Fat; Rosiglitazone; imunohistochemie; mužské pohlaví; dieta s vysokým obsahem tuků; Dietary Fats; Real-Time Polymerase Chain Reaction; bílá tuková tkáň; ELISA; Adipose Tissue, White; rosiglitazon; zánět; tukové buňky; dietní tuky; Enzyme-Linked Immunosorbent Assay; Animals; Thiazolidinediones; Energy Metabolism; Immunohistochemistry; Docosahexaenoic Acids; zvířata; myši inbrední C57BL; myši; Adipokines; Mice, Inbred C57BL; Mice; adipokiny